Spanish public libraries. Fesabid Report update - Arroyo-Vázquez, Natalia; Hernández-Sánchez, Hilario; Gómez-Hernández, José-Antonio (Anuario ThinkEPI, 2019)
The latest data published by the Ministry of Culture and Sports on Spanish public libraries, corresponding to the year 2017, are analyzed. They are compared with those of the 2010-2016 period, previously analyzed in the Fesabid Report. Public libraries in Spain: diagnosis after the economic crisis. In 2017, the first signs of recovery in the libraries began to be seen after a period of decline in indicators such as spending and use, which were resented during the economic crisis in Spain. Some trends continue as the greater weight of the local administration in the financing of libraries, responsible for more than three quarters of the expenses, and inter-territorial inequality, which occurs not only among autonomous communities, but also within same community.
Keywords: Public libraries; Spain; Economic crisis; Statistics.